Integrating Artificial Intelligence into Business Education: A Case Study of Curriculum Implementation - Nana Parulava; Nana Jikia (Scientific Research and Experimental Development, 2025)
This study examines the integration of artificial intelligence (AI) tools into business education. The course, designed for business students and formally approved by the rector, served as the subject of research to evaluate its implementation and outcomes. Findings highlight AI’s significance in resource allocation, decision-making, and business analytics. Student engagement and performance, including the use of various AI platforms and mini-projects, were analyzed as key indicators of the course’s effectiveness.